Elevation patterns of tree diversity, composition and stand structure in Mahendragiri Hill Forest, Eastern Ghats of Odisha, India - Swapna S. Khadanga; Ashaq Ahmad Dar; Neha Jaiswal; Prasad K. Dash; Shanmuganathan Jayakumar (Journal of Asia-Pacific Biodiversity, 2023)
Tropical mountain forests in Eastern Ghats provide a unique opportunity to relate environmental drivers to plant community structure along elevation gradient. We aimed to investigate the tree diversity, composition and stand structure along elevation gradient and drivers facilitating species distribution across Mahendragiri Hill Forest (MHF) in Eastern Ghats of Odisha, India. Altogether 120 plots of 0.05 ha were established and stems ≥10 cm diameter at breast height were measured. We compared species composition and stand structure among elevation zones. Ordination analysis was used to quantify how community structure was related to topographic, climatic and onsite conditions. In total 189 species representing 131 genera and 51 families were recorded ranging from 64 (MHF6) to 106 species (MHF4). Fabaceae representing 23 species, followed by Phyllanthaceae was dominant families. Maximum tree density and basal area were enumerated in high elevation MHF6 and least disturbed MHF5, respectively. Canonical Correspondence Analysis (CCA) interpreted 58.59% of variation and depicted the role of elevation followed by disturbance and precipitation in species distribution patterns. Variance partitioning analysis shows that topography and disturbance strongly partitioned the dissemination of tree species. Variations in species diversity reflects a direct coupling or interaction of several factors together, making it a complex phenomenon.